Biodiversity–ecosystem function relationships change through primary succession. Issue 11 (8th June 2017) - Mori, Akira S.; Osono, Takashi; Cornelissen, J. Hans C.; Craine, Joseph; Uchida, Masaki
Abstract : Ecologists traditionally use environmental parameters to predict successional shifts in compositional characteristics of local species assemblages (environmental control). Another important focus in ecology is to understand functional roles of species assemblages in determining local environmental properties (diversity control). Then, the question emerges: which is the cause, and which is the consequence? To clarify the causal relationships between species assemblages and environmental properties, we focused on seral changes in species/functional diversity of vascular plants in tundra ecosystems of the High Arctic. We found that, although species richness was influenced by soil properties in the earlier stages of primary succession, the causalities were reversed in the later stages. We also found functional differentiation among coexisting species in the later stage, suggesting that the 'complementarity effect' of diversity on ecosystem functions likely increased with ecosystem development through time. By contrast, particular species had little disproportional influence on soil properties, suggesting that the 'selection effect' as an alternative mechanism was less important. This result was likely attributed to the importance of facilitation in the marginal High Arctic environment. Plant–microsite associations are shaped by feedback mechanisms and therefore, neither plant nor microsite is a single absolute predictor of the other. Although our observational study has limitations, we demonstrates a possibility that the relative magnitude of the influence of one on the other can change in the process of succession, emphasizing that the causalities underlying biodiversity–ecosystem function relationships change through succession.